Clinical factors affecting minor amputation in diabetic foot disease at Tengku Ampuan Afzan Hospital, Kuantan - Afifi, Mustaqim; Zakaria@Mohamad, Zamzuri (2014)
Lower extremity amputation is a known complication of diabetic foot problem. In Singapore, Nather (2007) reported major amputation for diabetic foot problem was 27.2%, which is 20.3% BKA and 6.9% AKA. In Malaysia, Harwant (2000) reported 20% of diabetic foot patients in Kuala Lumpur Hospital had major amputation and higher prevalence of minor amputation about 31.7%. Minor amputation or limb salvage have better functional outcome. However, only few data available describing minor amputation and associated risk factors.